THE ROLE OF A LECTURER’S PERFORMANCE IN FACILITATING PROBLEM SOLVING FOR STUDENTS IN LEARNING TRANSLATION (A Case Study of a Good Lecturer at UKI Toraja, Indonesia) - Judith Ratu (UKI TORAJA, 2016)
The objectives of the research are to find out (i) the problems that the lecturer facesin teaching translation; (ii) the way of lecturer solves the problems in teachingtranslation. The researcher employed qualitative method in form of naturalisticapproaches for the study. The data resources for the research included one lecturerand students,. The instrument for the research consisted of observation, interviewand document file. In analyzing the data, the researcher employed cyclical modelby Miles and Huberman. The result showed that, (i) the problems that the lecturerfaced were from students themselves: lack of vocabulary, lack of knowledge ingrammar-structure, semantic, unmotivated student or passive students, studentswere difficult in looking up the word in the dictionary, the students tended to usetranslation machine and another problem was from outside the student was lack ofadvanced dictionary; (ii) the lecturer solved the problems by reviewing thematerial, simplifying the material by taking very close examples, using more thanone language in teaching, giving tips to translate, approaching the students byasking questions, organizing the class and providing quiz, exercises, assignments,and providing advanced dictionary, and comparing the use of translation theorythan translation machine in translating.